Barriers and facilitators to implementing community-based physical activity interventions: a qualitative systematic review - Jemima Cooper; Joey Murphy; Catherine Woods; Femke Van Nassau; Aisling McGrath; David Callaghan; Paula Carroll; Paul Kelly; Niamh Murphy; Marie Murphy; Irish Physical Activity Research Collaboration (I-PARC) (BMC, 2021)
Abstract Background Over the past decade several physical activity (PA) interventions have been shown to be efficacious in a controlled research setting, however there is a continued lack of evidence for how to successfully implement these PA interventions in real-world settings such as the community. This review aims to explore the barriers and facilitators that affect the implementation of community-based PA interventions and make recommendations to improve implementation from the included studies. Methods A systematic literature search of EBSCOhost, Scopus, PUBMED and Web of Science was conducted to identify articles that reported qualitative data on the implementation factors of community-based interventions where PA was a primary outcome. Data were extracted using the Consolidated Framework for Implementation Research (CFIR) as a guide. Implementation factors and recommendations were then mapped onto the 5 domains of the CFIR and synthesised thematically. Results From 495 articles, a total of 13 eligible studies were identified, with 6 studies using a mixed methods approach, and 7 reporting qualitative methods only. There were 82 implementation factors identified, including 37 barriers and 45 facilitators, and a further 26 recommendations from the papers across all 5 domains of the CFIR. More barriers than facilitators were identified within the CFIR domain inner setting, in contrast to all other domains where facilitator numbers outweighed barriers. Conclusions This review identified many facilitators and barriers of implementing physical activity interventions in the community. A key finding of this review was the impact of implementation strategies on successful implementation of community PA interventions. From the evidence, it was clear that many barriers to implementation could have been negated or reduced by an implementation plan in which several strategies are embedded. The findings of this review also suggest more attention to individual' skills and involvement is needed to improve self-efficacy and knowledge. The role of individuals across all organisational levels, from providers to leaders, can impact on the implementation of an intervention and its success. Trial registration PROSPERO - CRD42020153821 .